Harnessing bamboo waste for high-performance supercapacitors: A comprehensive review of activation methods and applications - Sharon Goh, Meng Xuang; Bridgid Chin, Lai Fui; Huang, Mee Mee; Yiin, Chung Loong; Jundika Candra, Kurnia; Lam, Su Shiung; Tan, Yie Hua; Chai, Yee Ho; Nor Adilla, Rashidi (Elsevier Ltd., 2024)
Commercial supercapacitors typically have low energy density, making them unsuitable for high energy demand applications. Then, the introduction and application of biomass-derived carbon materials have garnered attention in the industry due to its environmentally friendly nature and reliable performance. These carbon materials are favoured to be used as an electrode material due to their high specific surface area and specific capacitance. Bamboo biowaste, abundantly available in furniture and disposable utensils manufacturing industries, possesses favorable characteristics such as high nitrogen content, low oxygen content and a high graphitization degree. These properties make it a promising candidate for fabricating carbon materials suitable for supercapacitor applications. Recent studies indicated that bamboo-based supercapacitor has higher specific capacitance and higher performance than other carbon materials such as coconut shells. Therefore, numerous studies investigating this novel technology have been reported. Researchers have also made advancements in incorporating bamboo-based carbon materials in energy storage systems. The activation process is the key factor in enhancing the performance of the supercapacitors. However, findings from these studies, which are crucial for further development of this technology, have been scattered without a comprehensive compilation. Therefore, this review paper aims to provide a comprehensive overview of various activation techniques and specific applications of bamboo-derived activated carbon in supercapacitors. Despite recent advancements, challenges such as energy density issues and optimization over operating parameters remain. Addressing these challenges is crucial to fully understanding and realizing the potential of bamboo-derived supercapacitor.